2016
DOI: 10.1021/acs.joc.6b01096
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Diversity through a Branching Double-Annulation Cascade Strategy: Iminium-Induced One-Pot Synthesis of Diverse Fused Tetrahydroisoquinoline Scaffolds

Abstract: A branching double-annulation cascade (BDAC) strategy for diverse and complex fused THIQ scaffolds via a highly reactive iminium-induced one-pot double-cyclization sequence involving Pictect-Spengler-type cyclization has been developed for the first time. The salient features of this protocol are that it allows direct and rapid access to unprecedented diverse fused THIQ skeletons, is metal/catalyst free, has a cleaner reaction profile, provides good to excellent yields, and is a convenient approach. This catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…[289] Sharada et al reported one-pot synthesis of tetrahydroisoquinolines 477 using iminium-induced branching double annulation cascade (BDAC) protocol. [290] This methods falls into the category of Pictet-Spengler type cyclization which was reported for the first time. This unprecedented method gives an easy and facile entry to diverse range of fused tetrahydroisoquinolines (Scheme 291).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…[289] Sharada et al reported one-pot synthesis of tetrahydroisoquinolines 477 using iminium-induced branching double annulation cascade (BDAC) protocol. [290] This methods falls into the category of Pictet-Spengler type cyclization which was reported for the first time. This unprecedented method gives an easy and facile entry to diverse range of fused tetrahydroisoquinolines (Scheme 291).…”
Section: Non-metal Catalyzed Isoquinoline Synthesis and Other Methodsmentioning
confidence: 99%
“…In 2016, a one-pot process was reported from anthranilic acid and 2-haloethylbenzaldehydes through an iminium-mediated branching double-annulation cascade process. 5 Furthermore, alternative pathways proceed through cross-dehydrogenative coupling (CDC) from THIQ fused benzoic acids under various oxidative conditions. 6 Based on the CDC strategy, 7 Ye group developed an N-heterocyclic carbene-catalyzed domino reaction of THIQ-fused aryl aldehydes with phenyliodine( iii ) diacetate through acyl azolium intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…We will summarize the various quantum chemistry techniques that give insight into the (i) geometry, (ii) electronic structure, (iii) thermodynamics and (iv) kinetics properties of [NiFe] hydrogenase. In the process, we will touch on a range of technical challenges wide enough to be relevant to most other bioinorganic complexes in a variety of other research fields such as enzymology, [28][29][30][31][32] genetics, [33][34][35][36][37] regulation, [38][39][40][41] medicine [42][43][44][45][46] and environmental chemistry. [47][48][49][50] II.…”
Section: Introductionmentioning
confidence: 99%